Conference: The City – A Changeable (Un)certainty: Masaryk University, Faculty of Social Studies, Brno, Czech Republic, November 30 – Decemeber 1, 2007 - Bitušíková, Alexandra (Lidé města, 2008)
The Faculty of Social Sciences of Masaryk University in Brno organized a multidisciplinary conference, The City – a Changeable (Un)Certainty (Nov. 30 – Dec. 1, 2007). The goal of the conference was to open a forum for discussion on the meaning of the contemporary city and its various definitions. What is the city? How is it reflected by various disciplines? What impact does the (post-socialist, post-modernist) transformation of the city have on (in)equality, solidarity, social cohesion, inclusion/exclusion, and local/urban identities? How are the boundaries, public and private spaces, physical and social structure of the city created? These questions were in the core of the conference discussions.